Composition for pattern formation and method for pattern formation

A pattern-forming composition with a controlled Pr/Mr ratio and sugar derivative units improves etching processability, allowing for precise and complex pattern formation on substrates.

JP7605262B2Active Publication Date: 2024-12-24OJI HLDG CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023137001
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2024-12-24
Estimated Expiration
2039-09-20

AI Technical Summary

Technical Problem

Conventional methods for forming patterns on substrates using self-assembled compositions face poor etching processability, which hinders the formation of precise and complex semiconductor device patterns.

Method used

A pattern-forming composition is developed that includes a polymer with a specific free volume radius (Pr) to nuclear radius (Mr) ratio (2≦Pr/Mr≦3.3) and contains units derived from sugar derivatives, allowing for improved etching processability by introducing metals like Al into the pattern-forming film.

Benefits of technology

The composition enhances etching processability, enabling deeper substrate processing with higher etching selectivity, thus facilitating the formation of precise and complex patterns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605262000016
    Figure 0007605262000016
  • Figure 0007605262000001
    Figure 0007605262000001
  • Figure 0007605262000002
    Figure 0007605262000002
Patent Text Reader

Abstract

To provide a composition for forming a pattern, from which a film for forming a pattern showing excellent etching processability can be formed.SOLUTION: A composition for forming a pattern is a composition for forming a pattern comprising a polymer, and satisfies the condition of 2≤Pr / Mr≤3.3, where Pr represents the free volume radius of the polymer and Mr represents the nuclear radius of metal introduced upon forming a pattern from the composition for forming a pattern.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for pattern formation and a method for pattern formation. [Background technology]

[0002] Electronic devices such as semiconductors are required to have higher definition through miniaturization. In addition, diversification of shapes of patterns of semiconductor devices is also being considered. Known methods for forming such patterns include a double patterning method, a lithography method using an electron beam, a nanoimprint method, and a pattern formation method by self-organization using a directed self-assembly material (hereinafter also referred to as a self-organizing composition for pattern formation).

[0003] The self-assembling composition for pattern formation self-assembles by phase separation, so there is no need for an expensive electron beam lithography device, and the patterning process does not become complicated as in the double patterning method, so there is a cost advantage. As a self-assembling composition for pattern formation, for example, a diblock copolymer such as polystyrene-polymethyl methacrylate (PS-PMMA) is known (for example, Patent Document 1).

[0004] As the self-assembling composition for pattern formation, the use of materials other than PS-PMMA is also being considered. For example, Patent Document 2 discloses a self-assembling composition for pattern formation having a main chain of a styrene-based polymer, an acrylic-based polymer, or the like, and a group containing a hetero atom at the end of the main chain. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US2012 / 0241411 A1 [Patent Document 2] JP 2014-5325 A Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, after forming a pattern using the self-assembling composition for pattern formation, an etching step may be further carried out to process the pattern shape on a silicon wafer substrate using the pattern as a protective film. However, in the conventional method, there are cases where the etching processability is poor when processing the pattern shape on the substrate, which has been a problem.

[0007] Therefore, in order to solve such problems of the conventional technology, the present inventors have conducted studies with the aim of providing a pattern-forming composition capable of forming a pattern-forming film exhibiting excellent etching processability. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the inventors have found that etching processability when processing a pattern shape on a substrate can be improved by ensuring that the free volume radius of the polymer constituting the pattern-forming composition and the atomic nucleus radius of the metal introduced into the pattern-forming film formed from the pattern-forming composition satisfy specified conditions. Specifically, the present invention has the following configuration.

[0009] [1] A pattern-forming composition comprising a polymer, The free volume radius of the polymer is Pr. When the nuclear radius of the metal introduced when forming a pattern from the pattern-forming composition is Mr, A pattern-forming composition which satisfies the condition 2≦Pr / Mr≦3.3. [2] The pattern-forming composition according to [1], wherein the polymer contains a unit derived from a sugar derivative. [3] The composition for pattern formation according to [2], wherein the unit derived from a sugar derivative includes at least one selected from a structure represented by the following general formula (103) and a structure represented by the following general formula (104): [ka] [ka] In the general formulas (103) and (104), R 1 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group, an acyl group, an aryl group, a trimethylsilyl group, or a phosphoryl group; 1 may be the same or different; R 5 represents a hydrogen atom or an alkyl group; X 1 and Y 1 each independently represents a single bond or a linking group; r represents an integer of 1 or more, and the asterisk * represents R when r is 2 or more. 1 or R 1 Instead of R 1 represents the bonding site with any one of the oxygen atoms to which it is bonded. [4] The composition for pattern formation according to any one of [1] to [3], wherein the polymer further has a structure represented by the following general formula (105): [ka] In general formula (105), W 1 represents a carbon atom or a silicon atom, W 2 -CR 2 -, -O-, -S- or -SiR 2 - (wherein R represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and multiple R may be the same or different); R 11 represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyl group, and R 12 represents a hydrogen atom, a hydroxyl group, an acetyl group, a methoxycarbonyl group, an aryl group, an allyl group, a glycidyl ether group, a glycidyl ester group, an isocyanate ester group or a pyridyl group. [5] The composition for pattern formation according to any one of [1] to [4], wherein the polymer contains a unit derived from a sugar derivative, and the content of the unit derived from the sugar derivative in the polymer is 60 to 90 mass %. [6] The composition for pattern formation according to any one of [1] to [5], which is a mask material for pattern formation. [7] A step of applying a pattern-forming composition containing a polymer onto a substrate to form a pattern-forming film; A pattern forming method comprising the steps of: introducing a metal into at least a portion of the pattern forming film, The free volume radius of the polymer is Pr. If the nuclear radius of a metal is Mr, A pattern formation method that satisfies the condition 2≦Pr / Mr≦3.3. [8] The pattern forming method according to [7], further comprising the step of forming a pattern on the pattern forming film after the step of forming the pattern forming film. [9] The pattern forming method according to [7] or [8], further comprising an etching step after the step of introducing a metal. Effect of the Invention

[0010] According to the present invention, after a pattern-forming film is formed from a pattern-forming composition, etching processability can be improved when processing a substrate into a pattern shape. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram illustrating a process for forming a pattern on a substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, the substituents not specified as substituted or unsubstituted may have any substituent.

[0013] (Pattern forming composition) The present invention relates to a pattern-forming composition containing a polymer. A metal is introduced into a pattern-forming film formed from the pattern-forming composition of the present invention, and when the nuclear radius of the metal introduced into the pattern-forming film is Mr and the free volume radius of the polymer contained in the pattern-forming composition of the present invention is Pr, the condition of 2≦Pr / Mr≦3.3 is satisfied. Thus, the present invention relates to a pattern-forming composition containing a polymer having a free volume radius (Pr) that satisfies the above condition with respect to the nuclear radius (Mr) of the metal introduced in the pattern formation process.

[0014] Here, the nuclear radius (Mr) of the metal introduced into the pattern-forming film is a value cited from E Clementi, DL Raimondi, WP Reinhardt (1963) J Chem Phys. 38:2686. Note that when the metal introduced into the pattern-forming film is Al, 2 O 3 In the case of a metal oxide such as those mentioned above, it is sufficient that the atomic nuclear radius of the metal element (Al) satisfies the above condition.

[0015] The free volume radius (Pr) of the polymer is a value measured as follows. First, a polymer is dissolved in PGMEA so that the polymer and p-toluenesulfonic acid are 3% by mass and 0.3% by mass, respectively, to obtain a polymer solution sample. The polymer solution sample is then spin-coated onto a 2-inch silicon wafer substrate. After coating to a film thickness of 500 nm, the film is baked on a hot plate at 230°C for 5 minutes to form a pattern-forming film. Next, the positron annihilation lifetime of the formed pattern-forming film is measured to calculate the free volume radius (Pr) of the polymer. Specifically, the pattern-forming film is placed in a positron annihilation lifetime measurement device. A 22Na-based positron beam is used as the positron source, and BaF 2 The positron annihilation lifetime is measured under the following conditions using a scintillator and a photomultiplier tube manufactured by Fuji Invac Co., Ltd. As the positron annihilation lifetime measurement device, for example, a small positron beam generator PALS-200A manufactured by Fuji Invac Co., Ltd. can be used. Device constants: 263~272ps, 24.55ps / ch Beam intensity: 1.5keV Measurement depth: 0 to 25 μm (estimated) Measurement temperature: room temperature Measurement atmosphere: Vacuum Total count: Approximately 5,000,000 counts Sample pretreatment: Vacuum degassing at room temperature The positron annihilation lifetime curve obtained as above is analyzed by the nonlinear least squares program POSITRONFIT to calculate the average free volume radius, which is taken as the free volume radius (Pr) of the polymer.

[0016] The preferred free volume radius (Pr) of the polymer varies depending on the atomic nucleus radius of the metal introduced into the pattern-forming film, but for example, the free volume radius (Pr) of the polymer is preferably 0.10 nm or more, more preferably 0.20 nm or more, and even more preferably 0.25 nm or more. The free volume radius (Pr) of the polymer is preferably 0.50 nm or less, more preferably 0.40 nm or less, and even more preferably 0.35 nm or less. In order to set the free volume radius (Pr) of the polymer within the above range, for example, it is possible to adjust the content of the unit derived from the sugar derivative constituting the polymer, adjust the degree of polymerization of the sugar portion or the length of the sugar chain, or appropriately adjust the content of other constitutional units other than the unit derived from the sugar derivative.

[0017] The value of Pr / Mr may be 2 or more, preferably 2.1 or more, more preferably 2.2 or more, even more preferably 2.3 or more, and particularly preferably 2.4 or more. The value of Pr / Mr may be 3.3 or less, preferably 3.2 or less, more preferably 3.1 or less, and even more preferably 3.0 or less. By making the value of Pr / Mr within the above range, the permeability of the metal into the pattern-forming film can be increased, and thus a high-strength pattern-forming film can be formed. Therefore, after forming a pattern-forming film from the pattern-forming composition, the etching processability when processing a pattern shape on a substrate can be more effectively improved.

[0018] Here, the etching processability can be evaluated by calculating the etching selectivity, and the etching selectivity can be calculated, for example, as follows. To calculate the etching selectivity, first, the polymer is dissolved in PGMEA so that the polymer and p-toluenesulfonic acid are 3% by mass and 0.3% by mass, respectively, to obtain a polymer solution sample. Then, the polymer solution sample is spin-coated on a 2-inch silicon wafer substrate. After coating to a film thickness of 300 nm, the substrate is baked on a hot plate at 230° C. for 1 minute to form a film for pattern formation. Next, the substrate is masked with an ArF excimer laser exposure machine so as to have a line-and-space shape (line width 100 nm, space width 100 nm), and exposed using a commercially available ArF resist. After that, the substrate is baked on a hot plate at 105° C. for 1 minute, and then immersed in a developer to produce a line-and-space pattern. Next, this pattern sample is subjected to oxygen plasma treatment (100sccm, 4Pa, 100W, 60 seconds) in an ICP plasma etching device (Tokyo Electron Co., Ltd.) to form a line and space pattern in the pattern formation film. Thereafter, this pattern formation film is placed in an ALD (atomic layer deposition device: PICUSAN Corporation SUNALE R-100B) and is etched with TMA (trimethylaluminum, Al(CH 3 ) 3 ) gas is introduced for 300 seconds, and then water vapor is introduced for 150 seconds. This operation is repeated three times to form an Al film on the pattern formation film. 2 O 3 Using this pattern as a mask, hexafluoroethane (C 2 F 6) and Ar gas, plasma processing (100sccm, 0.4Pa, 200W, 120 seconds) is performed with an ICP plasma etching device (Tokyo Electron Co., Ltd.) to dry etch the silicon oxide film. The cross section of the silicon oxide film with the pattern formed before and after the plasma processing is observed with a scanning electron microscope (SEM) JSM7800F (JEOL Co., Ltd.) at an acceleration voltage of 1.5kV, an emission current of 37.0μA, and a magnification of 100,000 times. The thickness of the pattern forming film with the metal introduced and the depth processed into the silicon oxide film are measured, and the etching selectivity is calculated using the following formula. Etching selectivity=machining depth of silicon oxide film / (thickness of film for pattern formation before plasma treatment−thickness of film for pattern formation after plasma treatment) The etching selectivity is preferably greater than 2.0, more preferably 2.5 or more, even more preferably 3.0 or more, even more preferably 5.0 or more, and particularly preferably 10.0 or more. In this specification, when the etching selectivity is within the above range, it can be determined that the etching processability is good when processing a pattern shape on a substrate. In addition, when the etching processability is good, it is generally possible to deeply dig into the substrate.

[0019] In the present invention, the maximum metal content (atom%) when a metal is introduced into a pattern-forming film is preferably 15 atom% or more, more preferably 20 atom% or more, and even more preferably 25 atom% or more. The maximum metal content (atom%) when a metal is introduced into a pattern-forming film is calculated as follows. First, a polymer is dissolved in PGMEA so that the polymer and p-toluenesulfonic acid are 3 mass% and 0.3 mass%, respectively, to obtain a polymer solution sample. Then, the polymer solution sample is spin-coated on a 2-inch silicon wafer substrate. After coating to a film thickness of 300 nm, the substrate is baked on a hot plate at 230°C for 5 minutes to form a pattern-forming film. Next, the pattern-forming film is placed in an ALD (atomic layer deposition apparatus: SUNALE R-100B manufactured by PICUSAN Corporation) and heated at 95°C with TMA (trimethylaluminum, Al(CH3 ) 3 ) gas is introduced for 300 seconds, and then water vapor is introduced for 150 seconds. This operation is repeated three times to form an Al film on the pattern formation film. 2 O 3 Introduce Al. 2 O 3 The pattern-forming film after the introduction is placed in an XPS device (Nexsa XPS System manufactured by Thermo Fisher Scientific) and the concentration profile of the Al element in the film thickness direction is obtained by XPS analysis (X-ray photoelectron spectroscopy). 2 O 3 The thickness of the pattern-forming film after introduction is determined by scratching the sample surface with tweezers to expose the silicon substrate surface, forming a step, and measuring this step with a tactile step gauge (manufactured by Kosaka Manufacturing Co., Ltd., model number: ET-4000). In other words, the maximum metal content (atom%) is the metal content at the thickness where the largest amount of metal is contained in the thickness direction of the pattern-forming film.

[0020] Examples of metals to be introduced into the pattern-forming film include Li, Be, Na, Mg, Al, Si, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Rb, Sr, Y, Zr, Nb, Mo, Ru, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, La, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Tl, Pb, Bi, Po, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Among them, it is preferable to use Al, B, Si, Sn, Te, Zr, and W as the metals to be introduced into the pattern-forming film.

[0021] The pattern forming composition of the present invention is preferably a mask material for pattern formation. That is, the pattern forming film formed from the pattern forming composition of the present invention is preferably a protective film when etching a substrate. The pattern forming film formed from the pattern forming composition of the present invention is also expected to be effective in terms of gas permeability required for the nanoimprint method. Such a pattern forming film may be peeled off after the etching process.

[0022] The pattern forming composition of the present invention may be a self-assembly composition for pattern formation. In this specification, the term "directed self-assembly" refers to a phenomenon in which an organization or structure is constructed spontaneously, not only due to control from an external factor. For example, a self-assembly composition for pattern formation is applied onto a substrate, and annealing or the like is performed to form a film (self-assembly film) having a phase separation structure due to self-assembly, and a pattern can be formed on the substrate by removing a part of the phase in the self-assembly film. Such a pattern shape becomes a protective film, and it becomes possible to perform a desired etching process on the substrate.

[0023] (polymer) The pattern forming composition of the present invention preferably contains a polymer, and the polymer preferably contains a unit derived from a sugar derivative. The sugar derivative may be a sugar derivative derived from a monosaccharide, or may have a structure in which multiple sugar derivatives derived from monosaccharides are bonded. In addition, in a polymer containing a unit derived from a sugar derivative, the unit derived from the sugar derivative may be a structural unit having a structure derived from a sugar derivative in a side chain, or may be a structural unit having a structure derived from a sugar derivative in a main chain.

[0024] The unit derived from a sugar derivative is preferably at least one selected from a unit derived from a pentose derivative and a unit derived from a hexose derivative. The pentose derivative is not particularly limited as long as it has a structure derived from a pentose in which the hydroxyl group of the pentose of a known monosaccharide or polysaccharide is modified with at least a substituent. The pentose derivative is preferably at least one selected from a hemicellulose derivative, a xylose derivative, and a xylooligosaccharide derivative, and more preferably at least one selected from a hemicellulose derivative and a xylooligosaccharide derivative. The hexose derivative is not particularly limited as long as it has a structure derived from a known monosaccharide or polysaccharide hexose in which the hydroxyl group is modified with at least a substituent. The hexose derivative is preferably at least one selected from a glucose derivative and a cellulose derivative, and more preferably a cellulose derivative. Among these, the unit derived from a sugar derivative is preferably at least one selected from the group consisting of a unit derived from a cellulose derivative, a unit derived from a hemicellulose derivative, and a unit derived from a xylooligosaccharide derivative.

[0025] Among them, the unit derived from a sugar derivative preferably contains at least one selected from the structure represented by the following general formula (103) and the structure represented by the following general formula (104).

[0026] [ka] [ka]

[0027] In the general formulas (103) and (104), R 1 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group, an acyl group, an aryl group, a trimethylsilyl group, or a phosphoryl group; 1 may be the same or different. 5 represents a hydrogen atom or an alkyl group. 1 and Y 1Each independently represents a single bond or a linking group. r represents an integer of 1 or more, and the asterisk * represents R when r is 2 or more. 1 or R 1 Instead of R 1 represents the bonding site with any one of the oxygen atoms to which it is bonded.

[0028] In the general formulas (103) and (104), R 1 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group, an acyl group, an aryl group, a trimethylsilyl group, or a phosphoryl group; 1 may be the same or different. Among them, R 1 are preferably each independently a hydrogen atom or an acyl group having 1 to 3 carbon atoms. The above alkyl group also includes a sugar chain. That is, the sugar chain portion in the general formulae (103) and (104) may further have a branched chain.

[0029] R 1 When is an alkyl group or an acyl group, the number of carbon atoms can be appropriately selected depending on the purpose. For example, the number of carbon atoms is preferably 2 or more, and preferably 200 or less, more preferably 100 or less, even more preferably 20 or less, and particularly preferably 4 or less.

[0030] R 1 Specific examples of the alkyl group include acyl groups such as acetyl, propanoyl, butyryl, isobutyryl, valeryl, isovaleryl, pivaloyl, hexanoyl, octanoyl, chloroacetyl, trifluoroacetyl, cyclopentanecarbonyl, cyclohexanecarbonyl, benzoyl, methoxybenzoyl, and chlorobenzoyl; alkyl groups such as methyl, ethyl, propyl, butyl, and t-butyl. Among these, acetyl, propanoyl, butyryl, and isobutyryl groups are preferred, with acetyl being particularly preferred.

[0031] In the general formulas (103) and (104), R5 represents a hydrogen atom or an alkyl group. 5 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and particularly preferably a hydrogen atom or a methyl group.

[0032] In the general formulas (103) and (104), X 1 and Y 1 each independently represents a single bond or a linking group. X 1 When is a linking group, X 1 Examples of the alkylene group include -O- and -NH 2 -, carbonyl group, etc., but X 1 is preferably a single bond or an alkylene group having 1 to 6 carbon atoms, and more preferably an alkylene group having 1 to 3 carbon atoms. Y 1 When is a linking group, Y 1 Examples of Y include groups containing an alkylene group, a phenylene group, -O-, -C(=O)O-, etc. 1 may be a linking group combining these groups. 1 is preferably a linking group represented by the following structural formula:

[0033] [ka] JPEG0007605262000007.jpg6320

[0034] In the above structural formula, the * symbol indicates the bonding site with the main chain, and the * symbol indicates the bonding site with the sugar unit of the side chain.

[0035] In general formulae (103) and (104), r represents an integer of 1 or more, and may be 2 or more, or may be 3 or more. In addition, r is preferably 1500 or less, more preferably 1200 or less, even more preferably 500 or less, even more preferably 100 or less, particularly preferably 50 or less, and most preferably 10 or less.

[0036] The average degree of polymerization of the sugar units is the same as the preferred range of r above. The average degree of polymerization of the sugar units is the number of sugar units forming one sugar moiety, and when the sugar moiety has a side chain structure, the number of sugar units constituting the side chain is also included in the average degree of polymerization. The average degree of polymerization of the sugar units can be calculated by the following measurement method. First, the solution containing the sugar derivative is kept at 50°C and centrifuged at 15,000 rpm for 15 minutes to remove insoluble matter. The total sugar amount and the reducing sugar amount (both converted to xylose) of the supernatant are then measured. The average degree of polymerization is calculated by dividing the total sugar amount by the reducing sugar amount. If the above measurement method cannot be used, gel permeation chromatography, size exclusion chromatography, light scattering method, viscosity method, terminal group quantification method, sedimentation velocity method, MULDI-TOF-MS method, structural analysis method by NMR, etc. may be used. If the average degree of polymerization of the sugar units is measured after the copolymer synthesis, 1 The integral value of the peaks (around 3.3-5.5 ppm) derived from the sugar chain and the integral value of the peaks derived from other components of the sugar derivative are calculated by H-NMR, and the average degree of polymerization is calculated from the ratio of the integral values. 1 When is not a hydrogen atom, -OR 1 The integral value of the peak derived from the -OR group can also be used (in this case, 1 R in the group 1 is not a glycan).

[0037] In the general formulas (103) and (104), the * symbol indicates R when r is 2 or more. 1 or R 1 Instead of R 1 In other words, the polymerization site of the sugar unit in general formulas (103) and (104) is the R 1 Or R 1 Any one of the oxygen atoms to which R is bonded may be the polymerization site. 1When R is an alkyl group having a substituent, 1 may be a sugar chain, so even if there is one binding site marked with an * in general formulas (103) and (104), the sugar chain may actually have a side chain consisting of an additional sugar chain.

[0038] The unit derived from the sugar derivative contains at least one selected from the structure represented by the above general formula (103) and the structure represented by the above general formula (104), but preferably contains mainly the structure represented by the above general formula (103).This is because the structure represented by the above general formula (103) is more compact than the structure represented by the above general formula (104), which is believed to make it easier to control the free volume radius of the polymer.

[0039] The polymer contained in the pattern-forming composition of the present invention is preferably a copolymer. The copolymer may be a block copolymer, but is preferably a random copolymer. By using a random copolymer, a more uniform pattern-forming film can be formed.

[0040] When the polymer contained in the composition for pattern formation is a copolymer, it is preferable that the polymer further has a structure represented by the following general formula (105).

[0041] [ka]

[0042] In general formula (105), W 1 represents a carbon atom or a silicon atom. 1 is preferably a carbon atom. 2 -CR 2 -, -O-, -S- or -SiR 2 - (wherein R represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and a plurality of R may be the same or different). 2 HA-CR 2- is preferred, -CH 2 - is more preferable.

[0043] In general formula (105), R 11 R represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyl group. The alkyl group having 1 to 3 carbon atoms is preferably a methyl group, and R 11 is more preferably a hydrogen atom or a methyl group, and even more preferably a hydrogen atom.

[0044] In general formula (105), R 12 represents a hydrogen atom, a hydroxyl group, an acetyl group, a methoxycarbonyl group, an aryl group, an allyl group, a glycidyl ether group, a glycidyl ester group, an isocyanate ester group, or a pyridyl group. An allyl group is represented by -R 3 -CH=CH 2 The glycidyl ether group is preferably a group represented by -CH 2 OR 3 The glycidyl ester group is preferably a group represented by -COO-R 3 The isocyanate ester group is preferably a group represented by the formula -COO-R 3 It is preferable that R is a group represented by -NCO. 3 is an alkylene group which may have a substituent. Examples of the alkylene group which may have a substituent include -CH 2 -, -(CH 2 ) 2 -, -(CH 2 ) 3 -, -(CH 2 ) 4 -, -(CH 2 ) 5 -, -CH 2 OCH 2 -, -(CH 2 ) 2 OCH 2 -, -(CH 2 ) 3 OCH 2 -, -(CH 2 ) 4 OCH 2 -, -(CH2 ) 5 OCH 2 The alkylene group which may have a substituent may be a cycloalkylene group or a bridged cyclic cycloalkylene group.

[0045] Among them, R 12 is preferably a methoxycarbonyl group, an aryl group, a glycidyl ether group, a glycidyl ester group or a pyridyl group, more preferably a glycidyl ester group or an aryl group, and even more preferably a glycidyl ester group or a phenyl group. The phenyl group is also preferably a phenyl group having a substituent. Examples of phenyl groups having a substituent include a 4-t-butylphenyl group, a methoxyphenyl group, a dimethoxyphenyl group, a trimethoxyphenyl group, a trimethylsilylphenyl group, and a tetramethyldisilylphenyl group. In addition, R 12 It is also preferred that is a naphthalene group.

[0046] As mentioned above, R 12 is preferably a phenyl group, and in this case, the unit derived from the structure represented by general formula (105) is a unit derived from a styrene compound. Examples of the styrene compound include styrene, o-methylstyrene, p-methylstyrene, ethylstyrene, p-methoxystyrene, p-phenylstyrene, 2,4-dimethylstyrene, pn-octylstyrene, pn-decylstyrene, pn-dodecylstyrene, chlorostyrene, bromostyrene, trimethylsilylstyrene, hydroxystyrene, 3,4,5-methoxystyrene, and pentamethyldisilylstyrene. Among them, the styrene compound is preferably at least one selected from styrene and trimethylsilylstyrene, and more preferably styrene.

[0047] Also, R 12is also preferably a glycidyl ester group. In this case, the unit derived from the structure represented by general formula (105) is a unit derived from a glycidyl acrylate compound. Examples of the glycidyl acrylate compound include glycidyl acrylate, glycidyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether, and oxiran-2-ylmethyl-2-ethylidene pentanoate. Among them, the glycidyl acrylate compound is preferably at least one selected from glycidyl methacrylate and 4-hydroxybutyl acrylate glycidyl ether.

[0048] The weight average molecular weight (Mw) of the polymer is preferably 500 or more, more preferably 1000 or more, and even more preferably 1500 or more. The weight average molecular weight (Mw) of the polymer is preferably 1 million or less, more preferably 500,000 or less, even more preferably 300,000 or less, and even more preferably 250,000 or less. The weight average molecular weight (Mw) of the polymer is a value measured in terms of polystyrene by GPC.

[0049] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the polymer is preferably at least 1. Moreover, Mw / Mn is preferably at most 2, more preferably at most 1.5, and even more preferably at most 1.3. By setting Mw / Mn within the above range, the pattern-forming composition of the present invention can form a finer and better pattern structure with higher accuracy.

[0050] As described above, the polymer contains units derived from sugar derivatives, and the content of the units derived from sugar derivatives in the polymer is preferably 60% by mass or more, more preferably 70% by mass or more. The content of the units derived from sugar derivatives in the polymer is preferably 90% by mass or less, more preferably 85% by mass or less. By setting the content of the units derived from sugar derivatives in the polymer within the above range, the solubility in organic solvents can be increased.

[0051] The content of the unit represented by the general formula (105) in the polymer may be 5% by mass or more, or 10% by mass or more, based on the total mass of the polymer. The content of the unit represented by the general formula (105) in the polymer is preferably 40% by mass or less, and more preferably 30% by mass or less. The content of the unit represented by the general formula (105) in the polymer is 1 It can be calculated by H-NMR.

[0052] In addition to the above-mentioned structural units, the polymer may have other structural units, such as a lactic acid-derived unit, a siloxane bond-containing unit, an amide bond-containing unit, or a urea bond-containing unit.

[0053] (Polymer synthesis method) Polymer synthesis can be carried out by known polymerization methods such as living radical polymerization, living anionic polymerization, and atom transfer radical polymerization. For example, in the case of living radical polymerization, a polymer can be obtained by reacting a monomer with a polymerization initiator such as AIBN (α,α'-azobisisobutyronitrile). In the case of living anionic polymerization, a polymer can be obtained by reacting a monomer with butyllithium in the presence of lithium chloride.

[0054] The sugar portion of the sugar derivative as described above may be obtained by synthesis, or may be obtained by combining a step of extraction from lignocellulose derived from woody plants or herbaceous plants. When a method of extraction from lignocellulose derived from woody plants or herbaceous plants is adopted to obtain the sugar portion, the extraction method described in JP 2012-100546 A or the like can be used. Xylan can be extracted, for example, by the method disclosed in JP 2012-180424 A. Cellulose can be extracted, for example, by the method disclosed in JP 2014-148629 A.

[0055] When obtaining a sugar derivative, it is preferable to use the sugar moiety obtained by the above extraction method after modifying the OH group by acetylation, halogenation, etc. For example, when an acetyl group is introduced, an acetylated sugar derivative can be obtained by reacting with acetic anhydride.

[0056] The compound having the structure represented by the general formula (105) may be formed by synthesis, or a commercially available product may be used. When synthesizing the compound having the structure represented by the general formula (105), a known synthesis method may be adopted. When using a commercially available product, for example, Amino-terminated PS (Mw=12300 Da, Mw / Mn=1.02, manufactured by Polymer Source), allyl glycidyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.), glycidyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 4-hydroxybutyl acrylate glycidyl ether (manufactured by Mitsubishi Chemical Co., Ltd.), oxiran-2-ylmethyl-2-ethylidene pentanoate (manufactured by Achemica), 3,4-epoxycyclohexylmethyl methacrylate (manufactured by Daicel Corporation), etc. may be used.

[0057] The copolymer can be synthesized with reference to Macromolecules Vol. 36, No. 6, 2003. Specifically, a sugar derivative and a compound having a structure represented by general formula (105) are placed in a solvent containing DMF, water, acetonitrile, etc., and a reducing agent is added. The reducing agent is NaCNBH 3 Then, the mixture is stirred at 30°C to 100°C for 1 to 20 days, and a reducing agent is added as necessary. Water is added to obtain a precipitate, and the solid content is vacuum dried to obtain the copolymer.

[0058] In addition to the above-mentioned methods, examples of the copolymer synthesis method include synthesis methods using radical polymerization, RAFT polymerization, ATRP polymerization, click reaction, and NMP polymerization. Radical polymerization is a polymerization reaction that occurs by adding an initiator and generating two free radicals through a thermal or photoreaction. By heating a monomer (e.g., a styrene monomer and a sugar methacrylate compound in which methacrylic acid is added to the β-1 position at the terminal of a xylooligosaccharide) and an initiator (e.g., an azo compound such as azobisbutyronitrile (AIBN)) at 150°C, a polystyrene-polysaccharide methacrylate random copolymer can be synthesized. RAFT polymerization is a radical-initiated polymerization reaction that involves an exchange chain reaction using thiocarbonylthio groups. For example, the OH group at the terminal 1 position of xylooligosaccharides can be converted to a thiocarbonylthio group, and then styrene monomer can be reacted at 30°C to 100°C to synthesize a copolymer (Material Matters vol.5, No.1, Latest Polymer Synthesis, Sigma-Aldrich Japan Co., Ltd.). ATRP polymerization involves halogenating the terminal OH groups of sugars and reacting them with metal complexes [(CuCl, CuCl 2 , CuBr, CuBr 2 Alternatively, a sugar copolymer (e.g., a sugar-styrene block copolymer) can be synthesized by reacting a monomer (e.g., a styrene monomer) and a polymerization initiator (e.g., 2,2,5-trimethyl-3-(1-phenylethoxy)-4-phenyl-3-azahexane) with CuI (or CuI, etc.) + TPMA (tris(2-pyridylmethyl)amine), MeTREN (tris[2-(dimethylamino)ethyl]amine), etc.). In NMP polymerization, an alkoxyamine derivative is used as an initiator and heated to couple with monomer molecules and produce nitroxides. The polymerization reaction then proceeds as radicals are generated by thermal dissociation. This type of NMP polymerization is a type of living radical polymerization reaction. By mixing monomers (for example, styrene monomers and sugar methacrylate compounds in which methacrylic acid is added to the β-1 position at the end of xylooligosaccharides), using 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO) as an initiator, and heating at 140°C, a polystyrene-polysaccharide methacrylate random copolymer can be synthesized. The click reaction is a Cu-catalyzed 1,3-dipolar azide / alkyne cycloaddition reaction of propargyl-containing sugars.

[0059] (Method of manufacturing a pattern-forming composition) In the method for producing a pattern-forming composition, it is preferable to mix the above-mentioned polymer with a solvent. The solvent is preferably an organic solvent, and examples of the organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, sulfur-containing solvents, amide-based solvents, ester-based solvents, and hydrocarbon-based solvents. These solvents may be used alone or in combination of two or more.

[0060] Examples of alcohol-based solvents include methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, tert-butanol, n-pentanol, i-pentanol, 2-methylbutanol, sec-pentanol, tert-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, sec-hexanol, 2-ethylbutanol, sec-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, sec-octanol, n-nonyl alcohol, 2,6-dimethyl-4-heptanol, n-decanol, sec-undecyl alcohol, trimethylnonyl alcohol, sec-tetradecyl alcohol, sec- Examples of the alcohol include heptadecyl alcohol, furfuryl alcohol, phenol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, and diacetone alcohol; ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, 1H,1H-trifluoroethanol, 1H,1H-pentafluoropropanol, and 6-(perfluoroethyl)hexanol.

[0061] Examples of polyhydric alcohol partial ether solvents include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, ethylene glycol monophenyl ether, ethylene glycol mono-2-ethylbutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, and dipropylene glycol monopropyl ether.

[0062] Examples of ether solvents include diethyl ether, dipropyl ether, dibutyl ether, diphenyl ether, and tetrahydrofuran (THF).

[0063] Examples of ketone solvents include acetone, methyl ethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, diethyl ketone, methyl-i-butyl ketone, methyl-n-pentyl ketone, ethyl-n-butyl ketone, methyl-n-hexyl ketone, di-i-butyl ketone, trimethylnonanone, cyclopentanone, cyclohexanone, cycloheptanone, cyclooctanone, methylcyclohexanone, 2,4-pentanedione, acetonylacetone, acetophenone, and furfural.

[0064] An example of the sulfur-containing solvent is dimethyl sulfoxide.

[0065] Examples of amide solvents include N,N'-dimethylimidazolidinone, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropionamide, and N-methylpyrrolidone.

[0066] Examples of ester-based solvents include diethyl carbonate, propylene carbonate, methyl acetate, ethyl acetate, γ-butyrolactone, γ-valerolactone, n-propyl acetate, i-propyl acetate, n-butyl acetate, i-butyl acetate, sec-butyl acetate, n-pentyl acetate, sec-pentyl acetate, 3-methoxybutyl acetate, methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, benzyl acetate, cyclohexyl acetate, methylcyclohexyl acetate, n-nonyl acetate, methyl acetoacetate, ethyl acetoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, Examples of the monomer include diethylene glycol mono-n-butyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, glycol diacetate, methoxytriglycol acetate, ethyl propionate, n-butyl propionate, i-amyl propionate, methyl 3-methoxypropionate, diethyl oxalate, di-n-butyl oxalate, methyl lactate, ethyl lactate, n-butyl lactate, n-amyl lactate, diethyl malonate, dimethyl phthalate, and diethyl phthalate.

[0067] Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents such as n-pentane, i-pentane, n-hexane, i-hexane, n-heptane, i-heptane, 2,2,4-trimethylpentane, n-octane, i-octane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, trimethylbenzene, methylethylbenzene, n-propylbenzene, i-propylbenzene, diethylbenzene, i-butylbenzene, triethylbenzene, di-i-propylbenzene, n-amylnaphthalene, and anisole.

[0068] Among these, propylene glycol monomethyl ether acetate (PGMEA), N,N-dimethylformamide (DMF), propylene glycol monomethyl ether (PGME), anisole, ethanol, methanol, acetone, methyl ethyl ketone, hexane, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), 1H,1H-trifluoroethanol, 1H,1H-pentafluoropropanol, 6-(perfluoroethyl)hexanol, ethyl acetate, propyl acetate, butyl acetate, cyclohexanone, and furfural are more preferred, PGMEA or DMF are even more preferred, and PGMEA is even more preferred. These solvents may be used alone or in combination of two or more.

[0069] The content of the polymer in the pattern-forming composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, based on the total mass of the pattern-forming composition, and is preferably 30% by mass or less, based on the total mass of the pattern-forming composition.

[0070] <Optional ingredients> When producing a pattern-forming composition, an ionic liquid may be further blended as an optional component. An ionic liquid is a solvent that is liquid at 100° C. or less and is composed only of ions. At least one of the cation and anion moieties of the ions constituting the ionic liquid is composed of an organic ion.

[0071] By including an ionic liquid in the pattern-forming composition, the compatibility between the polymer and the organic solvent can be improved, and the ionic liquid also has the function of promoting phase separation of the block copolymer.

[0072] Ionic liquids are composed of a cation moiety and an anion moiety, and the cation moiety of the ionic liquid is not particularly limited, and may be any cation moiety generally used in ionic liquids. Preferred examples of the cation moiety of the ionic liquid include nitrogen-containing aromatic ions, ammonium ions, and phosphonium ions.

[0073] Examples of the nitrogen-containing aromatic cation include a pyridinium ion, a pyridazinium ion, a pyrimidinium ion, a pyrazinium ion, an imidazolium ion, a pyrazonium ion, an oxazolium ion, a 1,2,3-triazolium ion, a 1,2,4-triazolium ion, a thiazolium ion, a piperidinium ion, and a pyrrolidinium ion.

[0074] Examples of the anion portion of the ionic liquid include halogen ions, carboxylate ions, phosphinate ions, phosphate ions, phosphonate ions, and bis(trifluoromethylsulfonyl)imide ions, with bis(trifluoromethylsulfonyl)imide ions being preferred. Examples of the halogen ions include chloride ions, bromide ions, and iodide ions, with chloride ions being preferred. Examples of the carboxylate ions include formate ions, acetate ions, propionate ions, butyrate ions, hexanoate ions, maleate ions, fumarate ions, oxalate ions, lectate ions, and pyruvate ions, with formate ions, acetate ions, and propionate ions being preferred.

[0075] The pattern forming composition may contain, for example, a surfactant as an optional component. When the pattern forming composition contains a surfactant, the coating property to a substrate for pattern formation can be improved. Preferred surfactants include nonionic surfactants, fluorine-based surfactants, and silicone-based surfactants. These may be used alone or in combination of two or more.

[0076] The pattern forming composition may further contain a catalyst as an optional component. Examples of the catalyst include acid compounds such as p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridinium-p-toluenesulfonic acid, salicylic acid, sulfosalicylic acid, citric acid, benzoic acid, ammonium dodecylbenzenesulfonate, and hydroxybenzoic acid, and examples of the curing agent include ethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, dimethylaminopropylamine, m-xylylenediamine, m-phenylenediamine, triethylamine, and benzyldimethylamine.

[0077] The pattern-forming composition of the present invention may contain a monomer component constituting a polymer. For example, various monomers constituting a polymer can be appropriately added in order to improve the desired properties.

[0078] (Pattern formation method) The present invention also relates to a pattern forming method including the steps of applying a pattern forming composition containing the above-mentioned polymer onto a substrate to form a pattern forming film, and introducing a metal into at least a part of the pattern forming film. Here, when the free volume radius of the polymer is Pr and the atomic nucleus radius of the metal is Mr, the condition of 2≦Pr / Mr≦3.3 is satisfied. According to the pattern forming method of the present invention, it is possible to improve the etching processability when processing a pattern shape on a substrate after forming a pattern forming film from the pattern forming composition.

[0079] Examples of the substrate used in the pattern forming method of the present invention include substrates of glass, silicon, SiN, GaN, AlN, etc. Substrates made of organic materials such as PET, PE, PEO, PS, cycloolefin polymer, polylactic acid, and cellulose nanofiber may also be used. A plurality of layers made of different materials may also be sandwiched between the substrate and the guide pattern forming layer. The material is not particularly limited, but may be, for example, SiO 2 , SiN, Al 2 O 3 Examples of suitable materials include inorganic materials such as AlN, GaN, GaAs, W, SOC, and SOG, as well as organic materials such as commercially available adhesives.

[0080] The method for forming a pattern-forming film by applying the pattern-forming composition onto a substrate is not particularly limited, and examples thereof include a method for applying the pattern-forming composition to be used by a spin coating method or the like.

[0081] The pattern forming method of the present invention preferably further includes a step of forming a pattern on the pattern forming film after the step of forming the pattern forming film. In the step of forming a pattern, first, as shown in Fig. 1(a), a pattern forming composition is applied onto a substrate 10 to form a pattern forming film 20. Then, as shown in Fig. 1(b), at least a part of the pattern forming film 20 is removed so as to form a pattern shape to be formed on the substrate 10. For example, a resist film is laminated on the pattern forming film 20, and exposure and development treatments are performed to form a pattern shape as shown in Fig. 1(b).

[0082] Examples of the method for removing a part of the pattern-forming film include known methods such as reactive ion etching (RIE) such as chemical dry etching and chemical wet etching (wet development), sputter etching, and physical etching such as ion beam etching. The pattern-forming film can be removed by, for example, etching using tetrafluoromethane or perfluorocyclobutane (C 4 F 8), perfluoropropane (C 3 F 8 ), perfluoroethane (C 2 F 6 It is preferable to perform the etching by dry etching using a gas such as fluorine, boron trichloride, methane trifluoride, trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, chlorine, helium, sulfur hexafluoride, difluoromethane, nitrogen trifluoride, and chlorine trifluoride.

[0083] Also, a chemical wet etching process can be adopted as a process for removing a part of the pattern formation film. Examples of the wet etching method include a process of treating the film by reaction with acetic acid, a process of treating the film by reaction with a mixed solution of water and alcohol such as ethanol or i-propanol, and a process of treating the film with acetic acid or alcohol after irradiation with UV light or EB light.

[0084] In this manner, a pattern can be formed on the pattern-forming film. The pattern to be formed is preferably a line and space pattern, a hole pattern, or a pillar pattern.

[0085] The pattern forming method of the present invention includes a step of introducing a metal into at least a part of the pattern forming film. The step of introducing a metal is preferably performed after a pattern shape is formed in the pattern forming film, but the metal introducing step may be performed before the pattern shape is formed in the pattern forming film. Examples of the metal to be introduced into the pattern forming film include Li, Be, Na, Mg, Al, Si, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Rb, Sr, Y, Zr, Nb, Mo, Ru, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, La, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Tl, Pb, Bi, Po, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. The step of introducing a metal into the pattern-forming film can be carried out by, for example, the method described in Journal of Photopolymer Science and Technology Volume 29, Number 5 (2016) 653-657. When introducing a metal into the pattern-forming film, a method of using a metal complex gas, a method of applying a solution containing a metal, or a method of introducing a metal into a resist by an ion implant method can be adopted.

[0086] After the step of introducing a metal into at least a part of the pattern-forming film, an etching step is preferably further performed, which is a step of etching a substrate using the patterned pattern-forming film as a protective film (mask) as shown in Fig. 1(c).

[0087] Examples of the method for processing the substrate in the etching step include known methods such as reactive ion etching (RIE) such as chemical dry etching and chemical wet etching (wet development), sputter etching, and physical etching such as ion beam etching. 4 F 8 ), perfluoropropane (C 3 F 8It is preferable to perform dry etching using a gas such as fluorine, trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, chlorine, sulfur hexafluoride, difluoromethane, nitrogen trifluoride, and chlorine trifluoride.

[0088] In addition, the etching process may be a chemical wet etching process. Examples of wet etching methods include a method of treating the substrate by reaction with acetic acid, a method of treating the substrate by reaction with a mixed solution of water and alcohol such as ethanol or i-propanol, and a method of treating the substrate with acetic acid or alcohol after irradiation with UV light or EB light. EXAMPLES

[0089] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.

[0090] Example 1 [Synthesis of copolymer 1] (Synthesis of acetyl sugar methacrylate 1) 20g of xylose was added to a mixed solution of 250g of acetic anhydride and 320g of acetic acid, and stirred at 30°C for 2 hours. Approximately 5 times the amount of cold water as the solution was slowly added while stirring, and after stirring for 2 hours, it was left to stand overnight. 10g of precipitated crystals was added to a solution of 400mL of THF, 1.2g of ethylenediamine and 01.4g of acetic acid, and the temperature was adjusted to 0°C in a flask, and the solution was stirred for 4 hours. This was poured into 1L of cold water and extracted twice with dichloromethane. 20g of this extract, 300mL of dichloromethane and 4.8g of triethylamine were placed in a flask and cooled to -30°C. 2.8g of methacryloyl chloride was added and stirred for 2 hours. This was poured into 300mL of cold water, extracted twice with dichloromethane, and the solvent was concentrated to obtain 16.1g of acetyl xylose methacrylate 1. The structure of the obtained acetyl xylose methacrylate 1 is as follows.

[0091] [ka]

[0092] (Synthesis of acetylxylose methacrylate-styrene-glycidyl methacrylate random copolymer) 12.0g of acetyl methacrylate, 2.6g of styrene (Tokyo Chemical Industry Co., Ltd.), 2.6g of glycidyl methacrylate (Tokyo Chemical Industry Co., Ltd.), 100g of THF as a solvent, and 0.8g of azobisisobutyronitrile as a polymerization initiator were placed in a flask, and the glass container was sealed and heated to 78°C under a nitrogen atmosphere substituted with nitrogen, and stirred for 6.0 hours. After that, the temperature was returned to room temperature, and the inside of the glass container was placed under air, and the obtained solution was dropped into 300g of methanol to precipitate a polymer. Then, the solution containing the precipitated polymer was suction filtered to obtain 12g of white copolymer 1. The obtained copolymer 1 contains the following structural units.

[0093] [ka]

[0094] [Solution sample preparation] The copolymer 1 and the polymerization catalyst p-toluenesulfonic acid were dissolved in PGMEA so as to have a concentration of 3% by mass and 0.3% by mass, respectively, to obtain a polymer solution sample.

[0095] Example 2 [Synthesis of copolymer 2] (Synthesis of acetylxylose methacrylate-styrene-glycidyl methacrylate random copolymer) Copolymer 2 (12.0 g) was obtained in the same manner as in Example 1, except that the amount of styrene added in the synthesis of copolymer 1 was changed from 2.6 g to 2.3 g and the amount of glycidyl methacrylate added was changed from 2.6 g to 0.8 g. A polymer solution sample was also obtained in the same manner as in Example 1.

[0096] Example 3 [Synthesis of copolymer 3] (Synthesis of acetylxylose methacrylate-styrene random copolymer) Copolymer 3 (12.0 g) was obtained in the same manner as in Example 1, except that the amount of styrene added in the synthesis of copolymer 1 was changed from 2.6 g to 2.1 g and glycidyl methacrylate was not added. A polymer solution sample was also obtained in the same manner as in Example 1.

[0097] Example 4 [Synthesis of copolymer 4] (Synthesis of acetylxylotriose methacrylate-styrene random copolymer) Copolymer 4 (12.1 g) was obtained in the same manner as in Example 1, except that xylose was changed to xylotriose in the synthesis of copolymer 1. A polymer solution sample was also obtained in the same manner as in Example 1. The obtained copolymer 4 contains the following structural units. [ka]

[0098] [Analysis of copolymers] (ratio of unit (l):unit (m):unit (n)) 1 The ratio (mass ratio) of the units (l) and units (m):units (n) constituting the copolymer was determined and calculated by H-NMR. Specifically, 10 mg of the polymer was weighed and dissolved in 1 mL of deuterated chloroform to prepare an NMR solution, and the resulting solution was transferred to an NMR sample tube (Kanto Chemical Co., Ltd.) and analyzed by FT-NMR (JNM-ECZ600R: JEOL Co., Ltd.). 1 H-NMR measurements were performed.

[0099] [Evaluation of free volume radius] The obtained polymer solution sample was spin-coated onto a 2-inch silicon wafer substrate. After coating to a film thickness of 500 nm, it was baked on a hot plate at 230°C for 5 minutes to form a pattern-forming film. The pattern-forming film thus formed was further cut into 15 mm x 15 mm squares and placed in a small positron beam generator PALS-200A (thin film compatible positron annihilation lifetime measurement device) manufactured by Fuji Invac. A positron beam based on 22Na was used as the positron source, and BaF 2 The positron annihilation lifetime was measured under the following conditions using a scintillator and a photomultiplier tube manufactured by . Device constants: 263~272ps, 24.55ps / ch Beam intensity: 1.5keV Measurement depth: 0 to 25 μm (estimated) Measurement temperature: room temperature Measurement atmosphere: Vacuum Total count: Approximately 5,000,000 counts Sample pretreatment: Vacuum degassing at room temperature The positron annihilation lifetime curves obtained above were analyzed by the nonlinear least squares program POSITRONFIT to calculate the mean free volume radius.

[0100] [Evaluation of maximum metal introduction rate] The obtained polymer solution sample was spin-coated onto a 2-inch silicon wafer substrate. After coating to a film thickness of 300 nm, it was baked on a hot plate at 230°C for 5 minutes to form a film for pattern formation. The pattern-forming film thus formed is placed in an ALD (atomic layer deposition apparatus: PICUSAN SUNALE R-100B) and heated at 95°C to 1000°C with TMA (trimethylaluminum, Al(CH 3 ) 3 After introducing the gas for 300 seconds, water vapor was introduced for 150 seconds. This operation was repeated three times to form a pattern-forming film with Al. 2 O 3 was introduced. Al 2 O 3 The pattern-forming film after the introduction was placed in an XPS device (Nexsa XPS System manufactured by Thermo Fisher Scientific) and the concentration profile of the Al element in the film thickness direction was obtained by XPS analysis (X-ray photoelectron spectroscopy). 2 O3 The thickness of the pattern formation film after introduction was determined by creating a step by scratching the sample surface with tweezers to expose the silicon substrate surface, and measuring this step with a tactile step gauge (manufactured by Kosaka Manufacturing Co., Ltd., model number: ET-4000).

[0101] [Preparation of samples for measuring etching selectivity] The obtained polymer solution sample was spin-coated onto a 2-inch silicon wafer substrate with a silicon oxide film (film thickness 2 um). After coating to a film thickness of 300 nm, it was baked on a hot plate at 230°C for 1 minute to form a film for pattern formation. The mask was applied to the ArF excimer laser exposure machine to form a line and space shape (line width 100 nm, space width 100 nm), and exposure was performed using a commercially available ArF resist. After that, the film was baked on a hot plate at 105°C for 1 minute, and then immersed in a developer to create a line and space pattern. Next, this pattern sample was subjected to oxygen plasma treatment (100sccm, 4Pa, 100W, 60 seconds) in an ICP plasma etching device (Tokyo Electron Ltd.), whereby the photoresist was removed and a line and space pattern was formed in the pattern formation film. Thereafter, metal was introduced into the pattern formation film in the same manner as in the evaluation of the metal introduction rate of the copolymer. Using this pattern as a mask, hexafluoroethane (C 2 F 6 ) and Ar gas, plasma treatment (100 sccm, 0.4 Pa, 200 W, 120 seconds) was performed in an ICP plasma etching device (Tokyo Electron Ltd.) to perform dry etching of the silicon oxide film.

[0102] [Evaluation of etching processability] Hexafluoroethane (C 2 F 6The cross section of the silicon oxide film with the pattern formed before and after the plasma treatment using Ar gas was observed with a scanning electron microscope (SEM) JSM7800F (manufactured by JEOL Ltd.) at an acceleration voltage of 1.5 kV, an emission current of 37.0 μA, and a magnification of 100,000 times, and the thickness of the metal-introduced pattern forming film (thickness c in Fig. 1(b) and thickness c' in Fig. 1(c)) and the depth processed into the silicon oxide film (depth d in Fig. 1(c)) were measured. Then, the etching selectivity was calculated by the following formula. Etching selectivity=machining depth of silicon oxide film / (thickness of film for pattern formation before plasma treatment−thickness of film for pattern formation after plasma treatment) The etching processability was evaluated according to the following criteria. ◎: Etching selectivity is 10 or more ○: Etching selectivity is 2 or more and less than 10 ×: Etching selectivity is less than 2.

[0103] Example 5 In Example 1, when introducing a metal into the pattern-forming film, TMA (trimethylaluminum, Al(CH 3 ) 3 ) gas, instead of trimethyl borate (B(OCH 3 ) 3 Various evaluations were carried out in the same manner as in Example 1, except that a 200-kWh gas was used.

[0104] Example 6 In Example 1, when introducing a metal into the pattern-forming film, TMA (trimethylaluminum, Al(CH 3 ) 3 ) gas instead of trimethylantimony (Sb(CH 3 ) 3 Various evaluations were carried out in the same manner as in Example 1, except that a 200-kWh gas was used.

[0105] Comparative Example 1 In Example 1, when introducing a metal into the pattern-forming film, TMA (trimethylaluminum, Al(CH 3 ) 3) gas instead of trimethylindium (In(CH 3 ) 3 Various evaluations were carried out in the same manner as in Example 1, except that a 200-kWh gas was used.

[0106] Comparative Example 2 In Example 1, when introducing a metal into the pattern-forming film, TMA (trimethylaluminum, Al(CH 3 ) 3 ) gas, instead of trimethyl borate (B(OCH 3 ) 3 Various evaluations were carried out in the same manner as in Example 3, except that a 200-kWh or 250-kWh gas was used.

[0107] [Table 1]

[0108] In Table 1, the nuclear radii are values ​​based on those described in E Clementi, DL Raimondi, WP Reinhardt (1963) J Chem Phys. 38:2686.

[0109] In the examples, the condition 2≦Pr / Mr≦3.3 was satisfied, and therefore the etching processability was good. On the other hand, in the comparative examples, which did not satisfy the condition 2≦Pr / Mr≦3.3, the etching processability was poor. [Explanation of symbols]

[0110] 10 Substrate 20. Film for pattern formation

Claims

1. A pattern-forming composition containing a polymer and used to form a pattern-forming film into which a metal is introduced, comprising: the pattern-forming composition essentially consists of the polymer component, the polymer comprises a unit derived from a sugar derivative, and the content of the unit derived from the sugar derivative in the polymer is 60 to 90% by mass; the metal is Al; The free volume radius of the polymer measured by the following measurement method is Pr, When the nuclear radius of the metal is Mr, A pattern-forming composition satisfying the condition of 2.128≦Pr / Mr≦2.542; (Measurement method) The polymer is dissolved in PGMEA to give a polymer solution sample of 3% by mass and p-toluenesulfonic acid of 0.3% by mass; the obtained polymer solution sample is spin-coated onto a 2-inch silicon wafer substrate to give a film thickness of 500 nm, and then baked on a hot plate at 230°C for 5 minutes to form a pattern-forming film; the pattern-forming film is cut into a 15 mm x 15 mm square and placed in a thin-film compatible positron annihilation lifetime measurement device, and the positron annihilation lifetime is measured under the following conditions using a 22Na-based positron beam as a positron source and a BaF2 scintillator and a photomultiplier as a gamma-ray detector; the obtained positron annihilation lifetime curve is analyzed using the nonlinear least-squares program POSITRONFIT to calculate the mean free volume radius. Device constants: 263-272ps, 24.55ps / ch Beam intensity: 1.5 keV Measurement depth: 0 to 25 μm (estimated) Measurement temperature: room temperature Measurement atmosphere: vacuum Total count: Approximately 5,000,000 counts Sample pretreatment: Vacuum degassing at room temperature

2. A pattern-forming composition comprising a polymer and used for forming a pattern-forming film into which a metal is introduced, comprising: the pattern-forming composition essentially consists of the polymer component, the polymer comprises a unit derived from a sugar derivative, and the content of the unit derived from the sugar derivative in the polymer is 60 to 90% by mass; the metal is Sb; The free volume radius of the polymer measured by the following measurement method is Pr, When the nuclear radius of the metal is Mr, A pattern-forming composition having a Pr / Mr of 2.128; (Measurement method) The polymer is dissolved in PGMEA to give a polymer solution sample of 3% by mass and p-toluenesulfonic acid of 0.3% by mass; the obtained polymer solution sample is spin-coated onto a 2-inch silicon wafer substrate to give a film thickness of 500 nm, and then baked on a hot plate at 230°C for 5 minutes to form a pattern-forming film; the pattern-forming film is cut into a 15 mm x 15 mm square and placed in a thin-film compatible positron annihilation lifetime measurement device, and the positron annihilation lifetime is measured under the following conditions using a 22Na-based positron beam as a positron source and a BaF2 scintillator and a photomultiplier as a gamma-ray detector; the obtained positron annihilation lifetime curve is analyzed using the nonlinear least-squares program POSITRONFIT to calculate the mean free volume radius. Device constants: 263-272ps, 24.55ps / ch Beam intensity: 1.5 keV Measurement depth: 0 to 25 μm (estimated) Measurement temperature: room temperature Measurement atmosphere: vacuum Total count: Approximately 5,000,000 counts Sample pretreatment: Vacuum degassing at room temperature

3. The composition for pattern formation according to claim 1 or 2, wherein the unit derived from a sugar derivative includes at least one selected from a structure represented by the following general formula (103) and a structure represented by the following general formula (104): 【Chemistry 1】 【Chemistry 2】 In formulae (103) and (104), R 1 each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group, an acyl group, an aryl group, a trimethylsilyl group, or a phosphoryl group; 1 may be the same or different; R 5 represents a hydrogen atom or an alkyl group; X 1 and Y 1 each independently represents a single bond or a linking group; r represents an integer of 1 or more, and * represents R when r is 2 or more. 1 or R 1 Instead of R 1 represents the bonding site with any one of the oxygen atoms to which is bonded.

4. The composition for pattern formation according to any one of claims 1 to 3, wherein the polymer further has a structure represented by the following general formula (105): 【Chemistry 3】 In general formula (105), W 1 represents a carbon atom or a silicon atom, W 2 is -CR 2 -, -O-, -S- or -SiR 2 - (wherein R represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and multiple R may be the same or different); R 11 represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyl group; R 12 represents a hydrogen atom, a hydroxyl group, an acetyl group, a methoxycarbonyl group, an aryl group, an allyl group, a glycidyl ether group, a glycidyl ester group, an isocyanate ester group or a pyridyl group.

5. The pattern-forming composition according to any one of claims 1 to 4, which is a mask material for pattern formation.

Citation Information

Patent Citations

  • Self-organizing composition for pattern formation and pattern forming method

    JP2014005325A

  • Sequential infiltration synthesis for advanced lithography

    US20120241411A1

  • Lower layer film-forming composition, pattern forming method, copolymer, and monomer for lower layer film-forming composition

    WO2019163975A1